PENGARUH DINAMIKA HARGA ITEM DIGITAL TERHADAP STABILITAS EKONOMI DI MARKETPLACE GAME ONLINE - Nur Akbar Sulaiman; Muhammad Rifqi Naufal; Muhammad Dzaky Mubaraq; Nursobah Nursobah (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital economy has transformed online games into complex virtual markets, where digital items hold real monetary value. This price volatility raises concerns about the stability of the virtual economy. This study analyzes the impact of digital goods price dynamics on economic stability in online game markets and identifies key factors contributing to instability. A quantitative approach with an explanatory design was used, collecting data through a survey of 150 active online game players who transact digital items. Multiple linear regression was employed to assess the effects of price volatility, asset scarcity, and transaction volume on economic stability. The results indicate that price volatility negatively affects virtual economic stability (β = −0.47; p < 0.05), while asset scarcity (β = 0.32; p < 0.05) and transaction volume (β = 0.41; p < 0.01) positively impact stability. These findings suggest that uncontrolled price fluctuations reduce purchasing power and player confidence, while proper scarcity management and high transaction liquidity help stabilize the virtual economy. The study recommends that game marketplace developers implement price stabilization mechanisms, such as price floors and ceilings, regulate digital goods supply, and enhance transaction transparency and frequency to foster a stable, fair, and sustainable virtual economy.